Minimizing Risks of Liver Transplantation With Steatotic Donor Livers by Preferred Recipient Matching. Issue 8 (August 2020) - Jackson, Kyle R.; Motter, Jennifer D.; Haugen, Christine E.; Long, Jane J.; King, Betsy; Philosophe, Benjamin; Massie, Allan B.; Cameron, Andrew M.; Garonzik-Wang, Jacqueline; Segev, Dorry L.
Abstract : Background: Donor livers with ≥30% macrosteatosis (steatotic livers) represent a possible expansion to the donor pool, but are frequently discarded as they are associated with an increased risk of mortality and graft loss. We hypothesized that there are certain recipient phenotypes that would tolerate donor steatosis well, and are therefore best suited to receive these grafts. Methods: Using national registry data from the Scientific Registry of Transplant Recipients between 2006 and 2017, we compared 2048 liver transplant recipients of steatotic livers with 69 394 recipients of nonsteatotic (<30%) livers. We identified recipient factors that amplified the impact of donor steatosis on mortality and graft loss using interaction analysis, classifying recipients without these factors as preferred recipients. We compared mortality and graft loss with steatotic versus nonsteatotic livers in preferred and nonpreferred recipients using Cox regression. Results: Preferred recipients of steatotic livers were determined to be first-time recipients with a model for end-stage liver disease 15–34, without primary biliary cirrhosis, and not on life support before transplant. Preferred recipients had no increased mortality risk (hazard ratio [HR]: 0.92 1.041.16 ; P = 0.5) or graft loss (HR: 0.93 1.031.15 ; P = 0.5) with steatotic versus nonsteatotic livers. Conversely, nonpreferred recipients had a 41% increased mortality risk (HR: 1.17 1.411.70 ; P < 0.001) and 39% increased risk of graft loss (HR: 1.16 1.391.66 ; P < 0.001) with steatotic versus nonsteatotic livers. Conclusions: The risks of liver transplantation with steatotic donor livers could be minimized by appropriate recipient matching.